PENGARUH LABEL HALAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH(Studi Kasus Pada Grosir Kosmetik Sinar Fajar di Kecamatan Panyabungan Kabupaten Mandailing Natal) - Siti Khodijah; Rizka Ar Rahmah; Andy Hakim (BORJUIS: JURNAL OF ECONOMY, 2025)
The aim of the research is to determine the significant influence of the halal label on purchasing decisions for Wardah cosmetic products at Sinar Fajar Wholesale. The type of research is a purposive quantitative approach. The research population is Sinar Fajar Muslim consumers who use Wardah cosmetics. Sampling used the Non-Probability sampling method with Purposive Sampling technique. The aim of this research is to determine the influence of the halal label on purchasing decisions for Wardah cosmetics. This research is useful for researchers, society and future researchers. The type of research used in this thesis is quantitative descriptive. This research involved a sample of 100 respondents. Validity was tested using factor analysis, validity test, reliability test, scatterplot test, T test, coefficient of determination test using Cronbach's Alpa and data normality test using P-plot. The data analysis technique uses simple linear regression with the SPSS Version 21 program. The halal label variable (X) influences the purchasing decision variable (Y) of Wardah cosmetics with a significant t value of 0.000 which is smaller than 0.05, an R value of 0.774, and an R square value of 0.599, meaning that the halal label is able to explain the dependent variable or purchasing decision by 0.599 x 100% = 59.9 percent while the other 42.6 percent is explained by the lan variable. Based on the research results, it can be concluded that the influence of the halal label has a significant influence on purchasing decisions for Wardah cosmetics. With a value of tcount < ttable or tcount > ttable (12.111 < 1.66055 or 12.111 > 1.66055) and the halal label has a strong relationship with purchasing decisions of 0.59.9.